Reconsidering Al-Ghazali's Educational Thoughts in the Millennial Era - Munjahid, Munjahid (ALSYS, 2025)
Al-Ghazali, through his seminal work Iḥyā’ ‘Ulūm al-Dīn, has made enduring contributions to Islamic educational thought. However, certain aspects of his philosophy, such as the dichotomy of knowledge and the authoritative role of the teacher have sparked debate when examined in light of contemporary educational challenges. This study seeks to reassess the relevance of Al-Ghazali's educational philosophy within the context of the millennial generation, focusing on academic objectives, pedagogical approaches, epistemology, and the ethics governing educators and learners. Employing a qualitative, descriptive literature review method, the research analyzes Al-Ghazali’s primary texts alongside relevant secondary sources. Findings indicate that while Al-Ghazali’s educational paradigm shaped by his Sufi orientation, emphasizes character formation and spiritual development, several of his more traditional views warrant critical reevaluation. Specifically, the rigid classification of knowledge and the absolute authority of teachers may hinder adaptation to 21st-century educational demands, which prioritize creativity, collaboration, and technological integration. Nevertheless, core elements of his thought, such as the integration of moral values, the principle of gradual learning, and the emphasis on self-purification, remain pertinent to contemporary character education. Accordingly, Al-Ghazali’s educational philosophy continues to offer both inspiration and a critical framework for shaping a progressive and contextually grounded model of Islamic education in the millennial era.